Behavior of Using the Generation Z Sharia Investment Application in Surabaya City from the Perspective of the Unified Theory of Acceptance and Use of Technology (UTAUT) - Farhan Arif; N. Ari Subagio; Moch, Shulthoni (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2024)
Generation Z, especially those under 30 years old, dominates investments in the capital market with assets reaching IDR 52.36 trillion. Investment applications play a crucial role, particularly among the technologically adaptive Generation Z. Using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, this research analyzes the influence of performance expectations, effort expectations, social influence, and facilitating conditions on the behavior of using Sharia investment applications. The results show that performance expectations, effort expectations, and social influence significantly impact usage behavior while facilitating conditions have a lower influence. Simultaneously, all four variables collectively have a significant influence on the behavior of using Sharia investment applications